Pengaruh Kualitas Layanan Dan Fitur Terhadap Minat Penggunaan Berkelanjutan Mobil Banking BRI Dengan Kepuasan Pengguna Sebagai Variabel Intervening (Studi Pada Mahasiswa Universitas Muhammadiyah Metro Pengguna M-Banking BRI) - Ratmono, Ratmono; Yateno, Yateno; Putri, Annisa Nanda (Universitas Muhammadiyah Metro, 2023)
Bank Rakyat Indonesia (BRI) presents a banking application called BRI Mobile (BRIMo).The use of the Mobile Banking application also encountered various obstacles including thequality of the services provided in the application and related to features that can meet theneeds of customers in conducting financial transactions. This study aims to determine theeffect of service quality and features on interest in sustainable use with user satisfaction asan intervening variable for students using BRI Mobile Banking at Muhammadiyah MetroUniversity. The research design is quantitative research or verification research. Thevariables in this study are service quality, features, satisfaction and interest in continuoususe. The population and sample of the study were students of the Management StudyProgram, Faculty of Economics and Business, University of Muhammadiyah Metro Batch2018 with the number of samples taken as many as 68 students. Data collection techniquesusing questionnaires. The analytical tools used are data quality analysis and Path Analysiswith the SPSS program. The results showed that service quality, features and satisfactionpartially had a positive and significant effect on the interest in sustainable use. Satisfactiondoes not significantly increase the effect of service quality and features on interest insustainable use.